A bacteriochlorin-diketopyrrolopyrrole triad as a donor for solution-processed bulk heterojunction organic solar cells. Issue 31 (23rd July 2019) - Ponsot, Flavien; Bucher, Léo; Desbois, Nicolas; Rousselin, Yoann; Mondal, Pritam; Devillers, Charles H.; Romieu, Anthony; Gros, Claude P.; Singhal, Rahul; Sharma, Ganesh D.
Abstract : A bacteriochlorin-diketopyrrolopyrrole triad formally defined as an A–π–D–π–A electronic system is used as an efficient donor for bulk heterojunction solar cells, alone or combined to a diethynylpyrrole-based wide-bandgap small molecule donor. Abstract : We have designed an A–π–D–π–A small-molecule triad consisting of a bacteriochlorin (BC) donor central core linked with two diketopyrrolopyrrole (DPP) acceptors via ethynyl bridges (BC-DPP-1 ).BC-DPP-1 has a narrow optical bandgap of 1.38 eV with highest occupied molecular orbital and lowest unoccupied molecular orbital energy levels of −4.93 eV and −3.40 eV, respectively, and it was used as an electron donor along with [6, 6]-phenyl-C71 -butyric acid methyl ester (PC71 BM ) as an acceptor for solution-processed small-molecule organic solar cells. After optimizing the weight ratio betweenBC-DPP-1 andPC71 BM and pyridine as a solvent additive and subsequent solvent vapor annealing using THF, an organic solar cell based on the optimizedBC-DPP-1 :PC71 BM showed an overall power conversion efficiency of 7.48%. SinceBC-DPP-1 shows a weak absorption band in the 650–750 nm wavelength region, we used a second small molecule having strong absorption in this spectral region and prepared the ternary active layerBC-DPP-1 : SM : PC71 BM, varying the weight ratio between the two donors and keeping the amount ofPC71 BM constant. The ternary active layerBC-DPP-1 (70% w/w):SM (30% w/w):PC71 BM showed the best photovoltaic performance. After the optimization of the ternary active layer ( i.e., the solvent additive and subsequent solvent vapor additive), the organic solar cell showed overall power conversion efficiency of 9.88%. The improved power conversion efficiency resulted from the enhancement of J sc, V oc and FF as compared to the binary counterpart. Since BC is an analog of porphyrins and chlorophylls, these results demonstrate that benefiting from the narrow band gap ofBC-DPP-1 ( i.e., organic solar cells with light harvesting in the NIR region of the solar spectrum) can be a real improvement. Moreover, the low energy loss (0.48 eV) as compared to the binary counterpart (0.58 eV) also confirms the suppressed recombination in the ternary organic solar cells.